ปัญหาขอบเขตความรับผิดทางละเมิดของนายจ้างตามมาตรา 425 แห่งประมวลกฎหมายแพ่งและพาณิชย์ - พรรณนิษา สุขพันธุ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2015)
The purpose of this thesis is to study the scope of the employer’s tortious liability committed by hit employees according to section 425 of Civil and Commercial Code by comparing with laws and rules on employee’s tortious liability and the application of law in England, France and Germany, specifically, in the new course of works i.e., Outsourcing Service, Agency Worker and Freelance. From the study of Thai law, the vicarious liability of employer for his employee’s wrongful acts according to section 425 uses the word employer and employee which narrow down the application of law since the relationship between employer and employee is limited to hire of services in Section 575 only. Therefore, the new course of services is excluded. On the other hand, under English law, the scope of law is also limited to hire of services but the court can resolute such narrow application by creating implication law on hire of services. Thus, the vicarious liability can be applied broader. Meanwhile, under France and German law, the scope of liability is legislated broader than employer and employee. Hence, the liability in not limited to hire of services relationship and the vicarious liability can occur when the criteria set forth by law is met. When applying Section 425 with the course of services in society, if there is no relationship according to hire of services, Section 425 is not applicable to regulate the involving parties to be liable vicariously. In order to make involving parties be liable jointly with the one who committed wrongful acts, the writer suggests that the rules of liability should be similar to France and German law. When a person works for another’s benefit, being paid and the performance in under another’s command, even the absence of hire of services contract or power of command, the work for another person for some period of time should be sufficient for such person to be liable vicariously according to Section 425. Therefore, Section 425 should be amended by replacing the terms "employer and employee" with broader terms such as a person who uses another person to perform a task and worker so that the relationship will not be limited to hire of services only. Also, the rules of liability should be indicated clearly for applicability under Section 425 and the scope will be broadening to include new course of services.